Development of introductory teaching materials for the collaborative science laboratory of culture, Islam and technology - Suryandari Suryandari; Meyninda Destiara; Helda Rahmawati (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The development of introductory teaching materials for the collaborative science of culture, Islam, and technology is research that produces innovative teaching materials as references for introductory laboratory courses and similar subjects. This study aims to develop teaching materials and validate products by material experts and media experts. The development of teaching materials is carried out in stages: (1) enrichment of teaching materials by laboratory introductory materials in the curriculum of biology, physics, and chemistry study programs, (2) collecting local potential data that can be included and explained in teaching materials according to laboratory introductory materials, (3) explore information related to Islam-science according to the phenomena presented, (4) innovate material content by presenting 3D augmented reality technology which has explained the use and installation of supporting applications, (5) validate teaching materials on material and media aspects, (6) implement teaching materials in the introductory laboratory learning process and or laboratory management in physics, chemistry and biology study programs. This development research stage is in line with the ADDIE model development research. The validation results obtained a percentage of 79% for material experts and 88% for media experts who both belong to the